Auxin transport at cellular level: new insights supported by mathematical modelling - Hosek, Petr; Kubes, Martin; Lanková, Martina; Dobrev, Petre I; Klíma, Petr; Kohoutová, Milada; Petrásek, Jan; Hoyerová, Klára; Jirina, Marcel; Zazímalová, Eva (Journal of Experimental Botany, 2012)
The molecular basis of cellular auxin transport is still not fully understood. Although a number of carriers have been identified and proved to be involved in auxin transport, their regulation and possible activity of as yet unknown transporters remain unclear. Nevertheless, using single-cell-based systems it is possible to track the course of auxin accumulation inside cells and to specify and quantify some auxin transport parameters. The synthetic auxins 2,4-dichlorophenoxyacetic acid (2,4-D) and naphthalene-1-acetic acid (NAA) are generally considered to be suitable tools for auxin transport studies because they are transported specifically via either auxin influx or efflux carriers, respectively. Our results indicate that NAA can be metabolized rapidly in tobacco BY-2 cells. The predominant metabolite has been identified as NAA glucosyl ester and it is shown that all NAA metabolites were retained inside the cells. This implies that the transport efficiency of auxin efflux transporters is higher than previously assumed. By contrast, the metabolism of 2,4-D remained fairly weak. Moreover, using data on the accumulation of 2,4-D measured in the presence of auxin transport inhibitors, it is shown that 2,4-D is also transported by efflux carriers. These results suggest that 2,4-D is a promising tool for determining both auxin influx and efflux activities. Based on the accumulation data, a mathematical model of 2,4-D transport at a single-cell level is proposed. Optimization of the model provides estimates of crucial transport parameters and, together with its validation by successfully predicting the course of 2,4-D accumulation, it confirms the consistency of the present concept of cellular auxin transport.
Keywords: tabák; naftaleny; Indoleacetic Acids; kyselina 2,4-dichlorfenoxyoctová; Plant Growth Regulators; teoretické modely; kultivované buňky; Naphthalenes; Biological Transport; Nicotiana; biologický transport; Cells, Cultured; kyseliny indoloctové; regulátory růstu rostlin; Models, Theoretical; 2,4-Dichlorophenoxyacetic Acid